Bilateral ultrasound transversus abdominis plane block in a patient affected from Menkes disease - Dario Galante; Marco Caruselli; Francesco Dones; Salvatore Meola; Gianluca Russo; Giuseppe Pellico; Antonio Caso; Massimo Lambo; Flora Donadei; Giuseppe Mincolelli (MDPI AG, 2012)
This case report demonstrates the utility and safety of ultrasound transversus abdominis plane (TAP) block in a paediatric patient suffering from Menkes disease. Anaesthetists, and particularly paediatric and neonatal anaesthetists, have to make a careful assessment of these patients, who are subjected to frequent surgeries, despite their tender years. These operations are often necessary in order to improve the patient's quality of life as much as possible. The choice of anaesthetic technique must take the particular nature of the disease and the patient's medical history into consideration, while careful preparation and preoperative evaluations make it possible to administer the general or local anaesthetic safely. Official literature on the subject does not provide sufficient information about the use of local anaesthetic techniques. Moreover, the use of ultrasound TAP block in patients affected by Menkes disease has never been published in literature. In our experience, ultrasound TAP block has provided positive results, although the rarity of this childhood disease makes a detailed study difficult.